European Portuguese-Learning Infants Look Longer at Iambic Stress: New Data on Language Specificity in Early Stress Perception - Frota, Sónia; Butler, Joseph; Uysal, Ertugrul; Severino, Cátia; Vigário, Marina (Frontiers in Psychology, 2020)
The ability to perceive lexical stress patterns has been shown to develop in language-specific ways. However, previous studies have examined this ability in languages that are either clearly stress-based (favoring the development of a preference for trochaic stress, like English and German) or syllable-based (favoring the development of no stress preferences, like French, Spanish and Catalan), and/or where the frequency distributions of stress patterns provide clear data for a predominant pattern (like English and Hebrew). European Portuguese (EP) is a different type of language, which presents conflicting sets of cues related to rhythm, frequency and stress correlates that challenge existing accounts of early stress perception. Using an Anticipatory Eye Movement paradigm implemented with eye-tracking, EP-learning infants at 5-6 months demonstrated sensitivity to the trochaic/iambic stress contrast, with evidence of asymmetrical perception or preference for iambic stress. These results are not predicted by the rhythmic account of developing stress perception, and suggest that the language-particular phonological patterns impacting the frequency of trochaic and iambic stress, beyond lexical words with two or more syllables, together with the prosodic correlates of stress, drive the early acquisition of lexical stress. Our findings provide the first evidence of sensitivity to stress patterns in the presence of segmental variability by 5-6 months, and highlight the importance of testing developing stress perception in languages with diverse combinations of rhythmic, phonological and phonetic properties.